A graphical user interface (GUI) for an array of IP cameras - Yun, Li (2019)
Singapore is a country with high humidity and abundant rainfall. Over the past decade, the number of average rainy days per year is 166. Therefore a proper sewerage system is an essential part of Singapore public utilities. As years pass and water corrosion，it is inevitable that various defects, such as cracks and deformation, will occur in tunnels. Regular pipeline inspection and proper maintenance are important to prolong the service life of the tunnels. However, a traditional way of manual inspection and maintenance is inefficient and dangerous to human.